CD1a Reactivity in Non-neoplastic Adenohypophysis. (June 2016) - Pisapia, David J.; Rosenblum, Marc K.; Lavi, Ehud
Abstract : Within the differential diagnosis of patients presenting with sellar or suprasellar lesions is Langerhans cell histiocytosis (LCH). CD1a staining is frequently used to identify the presence of an abnormal proliferation of Langerhans cells on histologic sections and contributes to the diagnosis of LCH. Here, we report that the MTB-1 monoclonal antibody against the CD1a antigen reacts to native adenohypophyseal epithelial cells. We show that immunohistochemistry for CD1a exhibits strong positivity in all autopsy and surgically resected non-neoplastic adenohypophysis tested. Thus, CD1a positivity by itself should be interpreted with caution, and we recommend the routine use of a panel of stains including CD1a, Langerin, and synaptophysin in conjunction with morphologic analysis before a diagnosis of LCH is rendered. In addition, we find that pituitary adenomas fail to stain for CD1a prompting consideration of the utility of this stain as a marker for non-neoplastic gland. Abstract : Supplemental Digital Content is available in the text.